2021
DOI: 10.1155/2021/1999189
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Cervical Cancer according to HIV Status in Yaoundé, Cameroon

Abstract: Objective. To analyze the epidemiological aspects of invasive cervical cancer according to HIV status. Methods. This was an historical cohort study from January 2010 to April 2017 in three hospitals at the Yaoundé city Capital, Cameroon, after the National Ethics Committee’ approval. We included invasive cervical cancers with documented HIV status. Odds ratios and 95% confidence interval were calculated to assess the association between the different variables and HIV status. Survival was analyzed using the Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous epidemiologic studies have focused on the survival outcomes of patients with cervical cancer based on stage at diagnosis, access to treatment by surgery or chemoradiation, but few have compared survival outcomes by HIV status [ 8 , 9 , 11 , 12 ]. Furthermore, studies on survival outcomes by HIV status have reported inconsistent effects on cervical cancer mortality [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiologic studies have focused on the survival outcomes of patients with cervical cancer based on stage at diagnosis, access to treatment by surgery or chemoradiation, but few have compared survival outcomes by HIV status [ 8 , 9 , 11 , 12 ]. Furthermore, studies on survival outcomes by HIV status have reported inconsistent effects on cervical cancer mortality [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have focused on the survival outcomes of patients with cervical cancer based on stage at diagnosis, access to treatment by surgery or chemoradiation, but few have compared survival outcomes by HIV status [ 8 , 9 , 11 , 12 ]. Furthermore, studies on survival outcomes by HIV status have reported inconsistent effects on cervical cancer mortality [ 12 15 ]. This manuscript provides the descriptive epidemiologic characteristics of women diagnosed with invasive cervical cancer enrolled at 2 large tertiary academic medical centers in Nigeria, adding to previous survival data reported [ 9 ], expanding upon survival differences by HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have focused on the survival outcomes of patients with cervical cancer based on stage at diagnosis, access to treatment by surgery or chemoradiation, but few have compared survival outcomes by HIV status [8,9,11,12]. Furthermore, studies on survival outcomes by HIV status have reported inconsistent effects on cervical cancer mortality [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have focused on the survival outcomes of patients with cervical cancer based on stage at diagnosis, access to treatment by surgery or chemoradiation, but few have compared survival outcomes by HIV status [8,9,11,12]. Furthermore, studies on survival outcomes by HIV status have reported inconsistent effects on cervical cancer mortality [12][13][14][15]. This manuscript provides the descriptive epidemiologic characteristics of women diagnosed with invasive cervical cancer enrolled at 2 large tertiary academic medical centers in Nigeria, adding to previous survival data reported [9], expanding upon survival differences by HIV status.…”
Section: Introductionmentioning
confidence: 99%